2015
DOI: 10.5152/akd.2014.5796
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory arterial stiffness index is associated with impaired left atrial mechanical functions in hypertensive diabetic patients: A speckle tracking study

Abstract: Objective:The ambulatory arterial stiffness index has been proposed as an indicator of arterial stiffness. The aim of this study was to test the hypothesis that increased ambulatory arterial stiffness index might be related with impaired left atrial function in hypertensive diabetic patients with no previous history of cardiovascular disease.Methods:Inclusion criteria included office systolic BP> 130 mm Hg or diastolic BP> 80 mm Hg and absence of secondary causes of HT, whereas exclusion criteria LV ejection f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…28 Conversely, the data on analogous interactions with respect to left atrium performance are scarce. 29 This study provides incremental information over prior papers by a comprehensive analysis of an array of potential contributors to left atrium strain impairment in the early stage of HHD, as well as by a collective assessment of the relationships between central/peripheral haemodynamics and derangements of both function and size of the left atrium.…”
Section: Discussionmentioning
confidence: 99%
“…28 Conversely, the data on analogous interactions with respect to left atrium performance are scarce. 29 This study provides incremental information over prior papers by a comprehensive analysis of an array of potential contributors to left atrium strain impairment in the early stage of HHD, as well as by a collective assessment of the relationships between central/peripheral haemodynamics and derangements of both function and size of the left atrium.…”
Section: Discussionmentioning
confidence: 99%
“…Aix values were found to be correlated with serum asymmetrical dimethylarginine (ADMA) levels in newly diagnosed hypertensive patients ( 14 ). Furthermore, it has been previously shown that prediabetes and newly diagnosed diabetes patients have increased arterial stiffness and markers of ED through rising blood glucose levels ( 15 , 16 ). Increased PWV measurements in FMF patients may reflect increased cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in concordance with this study, but we evaluated the effects of lead exposure on arterial stiffness by using AASI, which was found to be significantly higher than that of the control group. As an indicator of arterial stiffness, AASI has been associated with an increased risk of cardiovascular morbidity and mortality in various clinical settings ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%